Numerical Framework to Determine Instability Modes for Static Vehicles under Partial Submergence - Hussain Shah, Syed Muzzamil (International Journal of Integrated Engineering, 2019)
Studies on instabilites of static (parked) vehicles that are partially submerged during flood events have captured worldwide attention in the previous years. The response of varying hydrodynamics effects to vehicles have been the interests reported. Indeed, the vehicle shapes have been found to significantly affect the response towards its hydrodynamics. These works, however, were experimental in nature. As the development of complex exterior designs of vehicles progressively made with the expansion of technologies, repeating the tedious experimental testing on another set of vehicle designs may not be practical. Herein this paper attempts to provide guidance on the use of a simple numerical framework to compensate the use of experimental testing. The proposed framework has been validated with a series of experimental testing conducted on a 1:24 scaled model that was controlled to be partially submerged under sub-critical conditions. Keeping close to the assumptions that the submergence levels of the vehicles are significantly influencing the buoyancy and drag forces, the numerical approach had given a simpler mechanism on the calculations of the submerged area (AD) and volume (V) of the vehicle, when this could not be computed easily during experiments. The parameters AD and V coupled with a graphical presentation of instability threshold values, would provide quick computations on the corresponding forces acting on the any similar characteristics static vehicle accordingly.